Simplifying
2k2 + 7k = 0
Reorder the terms:
7k + 2k2 = 0
Solving
7k + 2k2 = 0
Solving for variable 'k'.
Factor out the Greatest Common Factor (GCF), 'k'.
k(7 + 2k) = 0
Subproblem 1Set the factor 'k' equal to zero and attempt to solve:
Simplifying
k = 0
Solving
k = 0
Move all terms containing k to the left, all other terms to the right.
Simplifying
k = 0
Subproblem 2Set the factor '(7 + 2k)' equal to zero and attempt to solve:
Simplifying
7 + 2k = 0
Solving
7 + 2k = 0
Move all terms containing k to the left, all other terms to the right.
Add '-7' to each side of the equation.
7 + -7 + 2k = 0 + -7
Combine like terms: 7 + -7 = 0
0 + 2k = 0 + -7
2k = 0 + -7
Combine like terms: 0 + -7 = -7
2k = -7
Divide each side by '2'.
k = -3.5
Simplifying
k = -3.5Solutionk = {0, -3.5}